Error Analysis of the Students in Writing a Recount Text (A Case Study at Grade III in English Department Universitas HKBP Nommensen) - Bertaria Sohnata Hutauruk; Yanti Kristina Sinaga; Galina Sitinjak (Siliwangi University, 2022)
This research deals with the students’ error analysis in writing recount texts. This study aims to investigate the types of errors and the most dominant type of errors made by the third-grade students of the English department at UHN. This research applies qualitative research design. There were 31 students involved from the English department of Universitas HKBP Nommensen (UHN). The data were taken from their writing of recount texts. The results of the study showed that there are five types of errors made by the students, namely omission errors, addition errors, misformation errors, and misorder errors. In the students’ writing there were 13 omission errors (6.5%), 12 addition errors (6%), 158 misformation errors (79%), and 17 misorder errors (8.5%). Therefore, the most dominant type of error made by the third-grade students in English department of UHN in writing recount text is misformation error, with the total number of errors is 158 (79%). It can be concluded that the third-grade students in the English department at UHN is still low in writing recount text especially in using tenses.